PRODUCTIVITY, ADAPTABILITY AND GRAIN QUALITY OF MODERN UKRAINIAN WINTER TRITICALE CULTIVARS - G. V. Shchipak; Yu. V. Tsupko; A. P. Petrova; V. G. Shchipak (Вавиловский журнал генетики и селекции)
Grain-type winter triticale cultivars were studied in comparative long-term (2000–2009) trials in two agroeco logical zones of Ukraine. Since 1977, 16 triticale cultivars have been enrolled into the register in Ukraine, and their potential productivity has increased by 1.52 t/ha. Specialized winter triticale cultivars with optimal combinations of productivity, adaptive properties and improved technological parameters of grain quality have been raised by intraspecific hybridization methods. High winter hardiness is observed in cultivars Amphidiploid 42, Amphidiploid 52, Amphidiploid 256, and Garne (scores 7.5–8.0), and improved drought tolerance, in Amphidiploid 44, Kapriz, Raritet, and Amphidiploid 256. New multi-line cultivars Garne and Raritet show relatively high baking quality and overpower standard cultivar Amphidiploid 256 by 79–192 % in flour strength, by 26–39 % in bread volume recovery, and by 180–190 % in the overall baking quality index.